Natural forest regeneration through fire protection is a less imminent threat for truly stable savannas than afforestation - Brice Yannick Djiofack; Hans Beeckman; Nils Bourland; Basile Luse Belanganayi; Félix Laurent; Bhely Angoboy Ilondea; Laurent Nsenga; Alain Huart; Menard Mbende Longwwango; Victor Deklerck; Geert Lejeune; William W. M. Verbiest; et al. (Global Change Biology, 2024)

Protecting an artificial savanna as a nature‐based solution to restore carbon and biodiversity in the Democratic Republic of the Congo - Brice Yannick Djiofack; Hans Beeckman; Nils Bourland; Basile Luse Belanganayi; Félix Laurent; Bhely Angoboy Ilondea; Laurent Nsenga; Alain Huart; Menard Mbende Longwwango; Victor Deklerck; Geert Lejeune; William W. M. Verbiest; et al. (Global Change Biology, 2024)
A large share of the global forest restoration potential is situated in artificial ‘unstable’ mesic African savannas, which could be restored to higher carbon and biodiversity states if protected from human‐induced burning. However, uncertainty on recovery rates in protected unstable savannas impedes science‐informed forest restoration initiatives. Here, we quantify the forest restoration success of anthropogenic fire exclusion within an 88‐ha mesic artificial savanna patch in the Kongo Central province of the Democratic Republic of the Congo (DR Congo). We found that aboveground carbon recovery after 17 years was on average 11.40 ± 0.85 Mg C ha −1 . Using a statistical model, we found that aboveground carbon stocks take 112 ± 3 years to recover to 90% of aboveground carbon stocks in old‐growth forests. Assuming that this recovery trajectory would be representative for all unstable savannas, we estimate that they could have a total carbon uptake potential of 12.13 ± 2.25 Gt C by 2100 across DR Congo, Congo and Angola. Species richness recovered to 33.17% after 17 years, and we predicted a 90% recovery at 54 ± 2 years. In contrast, we predicted that species composition would recover to 90% of old‐growth forest composition only after 124 ± 3 years. We conclude that the relatively simple and cost‐efficient measure of fire exclusion in artificial savannas is an effective nature‐based solution to climate change and biodiversity loss. However, more long‐term and in situ monitoring efforts are needed to quantify variation in long‐term carbon and diversity recovery pathways. Particular uncertainties are spatial variability in socio‐economics and growing conditions as well as the effects of projected climate change.

Staphylococcus capitis isolated from bloodstream infections: a nationwide 3-month survey in 38 neonatal intensive care units - Marie Decalonne; Sandra Dos Santos; Rémi Gimenes; Florent Goube; Géraldine Abadie; Saïd Aberrane; Vanina Ambrogi; Raoul Baron; Patrick Barthelemy; Isabelle Bauvin; Olivier Belmonte; Emilie Benabid; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
To increase the knowledge about S. capitis in the neonatal setting, we conducted a nationwide 3-month survey in 38 neonatal intensive care units (NICUs) covering 56.6% of French NICU beds. We demonstrated 14.2% of S. capitis BSI ( S.cap BSI) among nosocomial BSIs. S.cap BSI incidence rate was 0.59 per 1000 patient-days. A total of 55.0% of the S.cap BSIs were late onset catheter-related BSIs. The S. capitis strains infected preterm babies (median gestational age 26 weeks, median birth weight 855 g). They were resistant to methicillin and aminoglycosides and belonged to the NRCS-A clone. Evolution was favorable in all but one case, following vancomycin treatment.